Community Empowerment in Wonodadi Village, Pringsewu - Yoeyong Rahsel; Andino Maseleno (Siber Journal of Advanced Multidisciplinary, 2025)
Community empowerment systems play a vital role in advancing human resources in Wonodadi Village. In practice, many residents of Wonodadi Village often face obstacles when attempting to improve their skills to increase family income. Therefore, this community service activity aims to transfer knowledge and self-improvement techniques to the community, both through the enhancement of existing businesses and educational guidance for students in Wonodadi Village. The methods employed include delivering instructional materials and practical application of existing business strategies—such as the use of social media—as well as providing educational guidance and introducing computer technology to students in Wonodadi Village. The results of the activity indicate that prior to this PKM, the community of Wonodadi Village had limited understanding of business strategies involving social media, and the students of Wonodadi Village were unfamiliar with computer technology. However, following the activity, it was observed that the community of Wonodadi Village began to try implementing new strategies in their businesses, particularly through social media. Likewise, students in Wonodadi Village now have a better understanding of computer technology, particularly the functions of computers. Thus, this PKM activity is expected to play a significant positive role in empowering the community of Wonodadi Village, especially in helping them improve their businesses, while in the field of education, students have gained better knowledge to shape their future in achieving their aspirations, particularly in the field of computer technology.